Utilización de árboles semánticos para la comprensión de textos especializados a partir de su terminología - Sevilla Muñoz, Manuel; Macías Otón, Elena (Anales de Filología Francesa, 2010)
In this article, we present a method to analyse and understand specialised texts through the developing of semantic trees from the terminology of the studied text. This terminology is organised into semantic fields according to criteria of semantic nature. In this way, terms, that are usually considered as one more difficulty of the specialised discourse, turn into a useful tool in order to know the conceptual content of a text and how such content is structured depending on one or several communicative purposes.